Mendelian randomization suggests non‐causal associations of testosterone with cardiometabolic risk factors and mortality. (26th August 2012) - Haring, R.; Teumer, A.; Völker, U.; Dörr, M.; Nauck, M.; Biffar, R.; Völzke, H.; Baumeister, S. E.; Wallaschofski, H.
Summary: Prospective studies showed that low serum testosterone concentrations are associated with various cardiometabolic risk factors and mortality. However, the causal nature of these associations is controversial. We studied 1 882 men aged 20–79 years with serum testosterone concentrations and genotyping data from the longitudinal population‐based Study of Health in Pomerania. Testosterone concentrations were cross‐sectionally associated with cardiometabolic risk factors, including anthropometric, lipid, blood pressure and glycaemic parameters; and prospectively with all‐cause mortality (277 deaths, 14.7%) during the 10‐year follow‐up. To overcome problems of residual confounding, reverse causation, or regression dilution bias in the investigated testosterone‐outcome associations, we used two‐stage least square regression models with previously identified polymorphisms at the SHBG gene (rs12150660) and X chromosome (rs5934505) as multiple genetic instruments in an instrumental variable (IV) approach, also known as Mendelian randomization. In standard regression analyses, testosterone was robustly associated with a wide range of cardiometabolic risk factors. In subsequent IV analyses, no such significant associations were observed. Similarly, prospective analyses showed a consistent association of low testosterone concentrations with increased all‐cause mortality risk, which was not apparent in subsequent IV analyses. The present Mendelian randomization analyses did not detect any evidence for causal associations of testosterone concentrations with cardiometabolic risk factors and mortality, suggesting that previously reported associations might largely result from residual confounding or reverse causation. Although testosterone assessment might improve risk prediction, implementation of testosterone replacement therapy requires further evidence of a direct effect on cardiometabolic outcomes from double‐blinded randomized controlled trials and large‐scale Mendelian randomization meta‐analyses.